A review of the genus Heterogomphus Burmeister, 1847 (Coleoptera: Scarabaeidae: Dynastinae: Oryctini) from Colombia - Moreno, Jhon C. Neita; Clavijo-Bustos, Julián; Ratcliffe, Brett C. (Zootaxa, 2025)
The 10 species of the genus Heterogomphus Burmeister recorded from Colombia are illustrated and diagnosed, and a species checklist and dichotomous keys to distinguish them are presented. Heterogomphus telamon (Burmeister, 1847) is reported for the first time for Colombia, and Heterogomphus onorei Voirin, 1984 is proposed as a new junior synonym of Heterogomphus curvicornis Prell, 1912. Finally, a new species from the Sierra Nevada de Santa Marta (Colombia) is described, Heterogomphus kogui Neita Moreno, Clavijo-Bustos, and Ratcliffe new species.